A Sociological Study of Behavior Pattern of Single Child Family: Examining the Impact of Single Child Family on Behavior Patterns and Socialization (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this study is to the Single child family has been becoming a family norm amonga substantial number of people. In an age when family groups are fundamentally changing, to understandthe interaction dynamics and its multi-faceted consequences on the behaviour pattern of children seemssignificant. There have been various stereo-typical beliefs in general about the personality and behaviorpattern of the single child as well as about the interaction dynamics in the single child family in thepresent culture. At the same time, growth of individualizing tendencies in the tiny households createsmajor concern about societal unity. Family being the primary agency of socialization has a great impactin shaping the new generation. It has been noticed that the parenting style and the socialization patternundergo changes with the changes in the structure of the family. Hence a sociological analysis of thesingle child family is expected to reveal many key insights into the socialization process in these newfamily formations. It has been found that whereas adolescence is proposed to be a period of storm andstress, its appearance is ultimately controlled by the individual socio- cultural surroundings. Hence inthe back drop of a relatively new family type such as single child household, study of the behaviorpattern of adolescents becomes particularly relevant. As per the empirical evidences, the downwardtrend in the fertility in India is neither driven by increasing childlessness nor by increasing number ofunmarried women. As the fall in marital fertility aiming at moulding of a high quality globalized childrenhave been highlighted as the key factor, it is likely to have substantial effect on the parent –childinteraction pattern in the small family.Further, the modern compact family is projected to exhibit a totallynew dynamics in the setting of shifting status, power and gender dimensions. But it can be also arguedthat the intricacies of modernity in many times turn out in effect as „King Midas‟ touch‟. The social worryabout the prospect of development of a generation weak in social skills from the individualizingenvironment of the nuclear family needs more careful research of emerging family configurations suchas single child family.